Childhood in the Shadow of War: Representation of War in Children’s Picture Books - Bednarek, Magdalena (Porównania, 2023)
The aim of the paper is to present four picture books published in Poland that concern the concept of war. These are The Enemy by D. Cali, S. Bloch, War by J.J. Letria and A. Letria, How War Changed Rondo by R. Romanyszyn and A. Łesiw, Bajka o Wojnie (The Fairytale on War) by J. Rudniańska and P. Fąfrowicz. This article examines how the books conceptualise the idea of war in three aspects: emotional, intellectual and historical. The analysis of visual and verbal content proves that the mentioned works affect mostly emotions. Anxiety caused by war seen as a destructive force is the main emotion created on the pages, and a happy ending is the way of excising it. Only one book, War, leaves the reader with this negative emotion. The Enemy, on the other hand, is the only book which contains an intellectual reflection about military conflict: the responsibility for its outbreak and individual commitment towards war. The presence of reflective component in books about war is not dependent on the age of the readers projected by publishers. The historical information is not present enough in the analysed books, but a universal perspective on the subject extenuates it. The main conclusion is that the presented books advocate an anti-war attitude through emotional influence, which, however, does not give the child readers a sense of security.